La Grande Sartreuse?: Re-citing Simone de Beauvoir in Feminist Theory - Rodier, Kristin (Atlantis, 2015)
This paper has two goals: to show why Clare Hemmings’ work, Why Stories Matter: The Political Grammar of Feminist Theory (2011), which focuses on the types and consequences of feminist “stories,” should be applied to Simone de Beauvoir; and to argue that Beauvoir’s place in the history of feminist thinking should be revisited. I propose to use some of the critical tools gleaned from Hemmings’ text to think through the place of Simone de Beauvoir in feminist theoretical storytelling.